Strategi Incumbent Parpol Mempertahankan Suara Pasca Pindah Partai Pada Pemilu Legislatif Kota Denpasar Tahun 2014 - Ning, Raqhuel Dominique; Erviantono, Tedi; Azhar, Muhammad Ali (Jurnal Nawala Politika, 2016)
ABSTRACT Incumbent Political Party Strategies Maintaining the Voters after Moving Political Parties In the legislative elections with a case study AANG Widiada reelected Post Moving from the Golkar Party to Nasdem as legislators Denpasar period 2014-2019. This research has been done in north Denpasar District. This research using qualitative method with descriptive type of analysis. Primary data was collected through interview technique purposive sampling and snowball sampling. Secondary Data obtained from news articles, the Internet, and books related to the study. The study refers to offensive and defensive strategies by Peter Schroder. The findings research is the offensive strategy implemented through Political Socialization Program and Performance Dharma Discourse at Pura Desa in Peguyangan village. Defensive strategies implemented through a mass ceremony of Memukur and Mesangih ceremony in Puri Peguyangan. Both of these strategies are winning strategies to pass the legislative elections in north Denpasar election area for the period 2014-2019. Keywords: Incumbent, Political Strategy, Denpasar Legislative election